IMPLEMENTATION OF ACCELERATION SYSTEMATIC LAND REGISTRATION FULL IN HUMBANG HASUNDUTAN DISTRICT - Ruslan Ruslan; Djauhari Djauhari (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
Land has a very important role for the community as a place of development and also the people's livelihood, especially in the state of Indonesia as the State Agriculture, so that the State Constitution RI Tahun1945 Article 33 paragraph (3) states that: "Earth, water, space, and wealth nature contained in it are controlled by the State and used for the greatest prosperity of the people ". As a follow up of Article 33 paragraph (3) that on September 24, 1960, enacted Law No. 5 of 1960 on Basic Regulation of Agrarian called by its official acronym BAL. Article 19 of Law No. 5 of 1960 stipulates that "to ensure legal certainty by the Government held land registration throughout the territory of the Republic of Indonesia in accordance with the provisions stipulated by Government Regulation", which was followed up with a given title deed as proof and evidence right, because it can ensure legal certainty for everyone. Then BAL is described by the issuance of PP 10 of 1961 on registration of land and replaced by Regulation No. 24 of 1997 on Land Registration Jo Minister of State for Agrarian Affairs / Head of National Land Agency No. 3 of 1997 on the Implementation of Government Regulation No. 24 of 1997 on Land Registration and based on Indonesian Presidential Regulation No. 17 of 2015 of the Ministry of Agricultural and Spatial jo Indonesian Presidential Regulation No. 20 Year 2015 concerning the National Land Agency, the Ministry of Agricultural and Spatial Planning / National Land Agency (KATR / BPN) is assigned to carry out government affairs in the area of land that is responsible to the Coordinating Ministry of Economic Affairs. Mentioned legal certainty in land registration is given a letter of proof of land rights called the title deed to the parties concerned as proof and evidentiary tool for rights to lands that held them. Implementation of registration of land in modern society is the duty of the State carried out by the government for the people's interest in ensuring legal certainty in the field of land. Right to control the state for land, water and air space in Indonesia is the devolution of the elements of the public of the rights of the nation, while the right of the people on the earth, water and air space of Indonesia, is a right of the people of Indonesia, as Haqul of God given to Haqul Adam (Indonesianpeople). That until the moment of registration of land in Indonesia has reached ± 54 (fifty-four) million plot of ± 85 (eighty-five) million parcels of land (data from the Center for Data and Information Land November 11, 2015) because since 1981 carried out land registration the first time en masse on the issuance of certificates of land rights as a letter of proof of the rights which a proofing tool that is powerful, through the Strategic Program as Prona, Agricultural land, fisherman, Micro, Small, Low-Income Communities, redistribution of land, Consolidation Land, Transmigration and others which are land development activities for Indonesian citizens or legal entities / social and religious organizations, preferred to the economically weak to medium. 2017 has been issued Regulation of the Minister of Agriculture of Dan Spatial / Head of National Land Agency Number 1 Year 2017 on the Acceleration of the Implementation of the Land Registration Systematic Full of Changes to the Regulation of the Minister of Agriculture and Spatial Planning / Head of National Land Agency No. 35 Year 2016 on the Acceleration implementation of the land Registry Systematic Complete, which aims to provide legal certainty and legal protection of land rights of the people in a fair and equitable, and promote economic growth in general and the people's economy in particular, as well as reduce the incidence of land disputes in the future so it needs to be accelerated registration complete a systematic land in all regions of the Republic of Indonesia, especially in Humbang Hasundutan.